Inter-ethnic dating preferences of Roma and non-Roma secondary school students - László Lőrincz (Hungarian Academy of Sciences, Institute of Economics, 2015)
Adolescent romantic relationships are sources of social influence concerning educational achievement and delinquent behavior. Integrated schooling is known to induce inter-ethnic friendship relations, however, it also creates the opportunity of inter-ethnic dating. Based on contact theory, inter-ethnic personal relationships or long-term exposure decreases ethnic prejudice, thus it is proposed that willingness to date between ethnic groups may also increase. The question arises, whether in the school context exposure is enough for this mechanism to emerge, or personal contact is necessary. It must be also taken into account, that romantic relationships are embedded in status relations within schools. Previous studies on intermarriage and homogamy found a "social exchange" mechanism, that lower status members of majority groups are more likely to choose minority partners. Translated to the adolescent society, it is assumed, that the less popular members of the majority groups are those, who are more willing to form inter-ethnic dating relations. To address the above questions empirically, the first wave of the Hungarian network panel "Wired into Each Other" was analyzed, containing data of 1214 9th grade students in 43 classes of seven secondary schools. Inter-ethnic dating preferences of Roma and non-Roma students were measured by dyadic attribution of physical attractiveness, and nominations of willingness to date. Statistical analysis was carried out using multilevel p2 models. They suggest that mixed groups are not sufficient, but personal contacts are necessary to decrease same ethnicity preferences in dating. An additional tendency is that among majority students, those who are isolated from the friendship networks are the ones who are more willing to date with the minority group.
Keywords: J13; J15; 330; romantic relationships; dating; intergroup contact; adolescents; Roma minority; Hungary